2014
DOI: 10.1093/gerona/glu133
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K Antagonists and Cognitive Impairment: Results From a Cross-Sectional Pilot Study Among Geriatric Patients

Abstract: We found more frequent cognitive impairment associated with the use of VKAs, specifically fluindione, among geriatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 14 publications
1
21
1
1
Order By: Relevance
“…Consistently, a link between the use of VKAs and worse cognitive performance was previously highlighted in older adults [7]. These results were confirmed in three longitudinal studies reporting greater cognitive decline and executive dysfunction among those using VKA, even after adjustment for a history of atrial fibrillation and stroke [8-10].…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Consistently, a link between the use of VKAs and worse cognitive performance was previously highlighted in older adults [7]. These results were confirmed in three longitudinal studies reporting greater cognitive decline and executive dysfunction among those using VKA, even after adjustment for a history of atrial fibrillation and stroke [8-10].…”
Section: Introductionsupporting
confidence: 68%
“…In humans, clinical epidemiological studies have shown associations of the use of VKAs with cognitive disorders [5, 7] and decline of executive functions [8, 9]. Conversely, very few studies have examined the impact of the use of VKAs on brain structure.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that individuals with AD often have low serum concentrations of vitamin K [63][64][65]. Furthermore, geriatric patients that use vitamin K antagonists as anticoagulant medications suffer more frequent cognitive impairment than patients not prescribed these medications [66]. Vitamin K is involved in neuron development and survival through anti-apoptotic and anti-inflammatory effects which are mediated by Gas 6, protein S, and sphingolipids [67].…”
Section: Vitamin Kmentioning
confidence: 99%
“…A possible role of vitamin K in AD-pathogenesis is further given by the discovery of a positive correlation between the serum vitamin K level and the cognitive functions of AD patients [147,148]. Additionally, the use of vitamin K antagonists as anticoagulant medications is associated with a more frequent cognitive impairment among geriatric patients [149]. …”
Section: Vitamin Kmentioning
confidence: 99%